2009
DOI: 10.1111/j.1365-246x.2009.04077.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in magmatic processes along the East Greenland volcanic margin

Abstract: S U M M A R YSeismic velocities and the associated thicknesses of rifted and igneous crust provide key constraints on the rifting history, the differentiation between non-volcanic and volcanic rifted margins, the driving force of magmatism at volcanic margins, that is, active or passive upwelling and the temperature anomaly in the lithosphere. This paper presents two new wideangle seismic transects of the East Greenland margin and combines the velocity models with a compilation of 30-wide-angle seismic velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 90 publications
6
83
0
Order By: Relevance
“…HVLC can make up a large part of the total magmatic output along volcanic rifted margins, and as studies in the North Atlantic have shown, variations in size and physical properties of the HVLC in these settings hold important clues to mantle melting scenarios (Fernàndez et al, 2010;Kelemen and Holbrook, 1995;Korenaga et al, 2002;Ridley and Richards, 2010;Voss et al, 2009;White et al, 2008). Alternatively, it might be speculated that portions of the HVLC form postrift (Franke, 2013).…”
Section: K Becker Et Al: Asymmetry Of High-velocity Lower Crust On mentioning
confidence: 99%
“…HVLC can make up a large part of the total magmatic output along volcanic rifted margins, and as studies in the North Atlantic have shown, variations in size and physical properties of the HVLC in these settings hold important clues to mantle melting scenarios (Fernàndez et al, 2010;Kelemen and Holbrook, 1995;Korenaga et al, 2002;Ridley and Richards, 2010;Voss et al, 2009;White et al, 2008). Alternatively, it might be speculated that portions of the HVLC form postrift (Franke, 2013).…”
Section: K Becker Et Al: Asymmetry Of High-velocity Lower Crust On mentioning
confidence: 99%
“…Average half-spreading rates (29-33 km/Myr) and crustal thicknesses at this time were at their highest observed values (Fig. 3, Breivik et al, 2006Smallwood and White, 2002;Voss et al, 2009). For example, oceanic crustal thickness was ∼8 km along the early AR (Breivik et al, 2006), as thick or thicker along much of the RR, and significantly thicker (>30 km) along the Iceland-Greenland and IcelandFaeroe volcanic ridges (e.g.…”
Section: Introductionmentioning
confidence: 89%
“…3). During 43-28 Ma, seafloor spreading at the AR was probably slower than at the RR and MR by as much as 30% (Breivik et al, 2006;Mosar et al, 2002;Smallwood and White, 2002;Voss et al, 2009), likely related to lithospheric stretching or the very earliest stages of rifting at the KR. Crustal thickness generated from 43 to 28 Ma along the middle and northern portions of the AR was only 3.5-5.5 km (Breivik et al, 2006), similar to that of normal (not hotspot influenced) oceanic crust at the same ultra-slow spreading rate of ∼7 km/Myr (Dick et al, 2003;White et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations